Exploring the dimensions of school bullying: perceptions, gender differences, and learning impacts among secondary school students / Nurul Amira Yusaini, Nor Hafizah A Hamid and Zarith Sofiah Othman - Yusaini, Nurul Amira; A Hamid, Nor Hafizah; Othman, Zarith Sofiah (Universiti Teknologi MARA, Kedah, 2024)
Bullying remains a persistent and complex issue within school environments, impacting the physical, emotional, and psychological well-being of students worldwide. This research aims to investigate students’ perspectives on school bullying and its impact on the quality of learning. Students’ viewpoints are divided into three dimensions: the ability to bully, the reason for bullying, and the prevention of bullying at school. By using the quantitative approach, data are collected through a questionnaire from a sample of 150 students in a secondary school in Johor, Malaysia. A Likert scale was used to gauge students’ perceptions of school bullying and its effects on learning quality. The findings reveal that a significant number of school students were least inclined to engage in bullying activities. In fact, there is no significant difference between genders in the students’ perceptions of school bullying. However, there is a significant difference between genders in their perception about its effect, particularly on the victims’ mental state. The findings can be a source of reference for the Ministry of Education or any